P16‐positive lymph node metastases from cutaneous head and neck squamous cell carcinoma: No association with high‐risk human papillomavirus or prognosis and implications for the workup of the unknown primary. Issue 8 (16th February 2016) - McDowell, Lachlan J.; Young, Richard J.; Johnston, Meredith L.; Tan, Tze‐Jian; Kleid, Stephen; Liu, Chen S.; Bressel, Mathias; Estall, Vanessa; Rischin, Danny; Solomon, Benjamin; Corry, June
Abstract : BACKGROUND: The incidence of p16 overexpression and the role of human papillomavirus (HPV) in cutaneous head and neck squamous cell carcinoma (cHNSCC) are unclear. METHODS: One hundred forty‐three patients with cHNSCC lymph node metastases involving the parotid gland were evaluated for p16 expression by immunohistochemistry. The detection of 18 high‐risk HPV subtypes was performed with HPV RNA in situ hybridization for a subset of 59 patients. The results were correlated with clinicopathological features and outcomes. RESULTS: The median follow‐up time was 5.3 years. No differences were observed in clinicopathological factors with respect to the p16 status. p16 was positive, weak, and negative in 45 (31%), 21 (15%), and 77 cases (54%), respectively. No high‐risk HPV subtypes were identified, regardless of the p16 status. The p16 status was not prognostic for overall (hazard ratio, 1.08; 95% confidence interval [CI], 0.85‐1.36; P = .528), cancer‐specific (hazard ratio, 1.12; 95% CI, 0.77‐1.64; P = .542), or progression‐free survival (hazard ratio, 1.03; 95% CI, 0.83‐1.29; P = .783). Distant metastasis‐free survival, freedom from locoregional failure, and freedom from local failure were also not significantly associated with the p16 status. CONCLUSIONS: p16 positivity is common but not prognostic in cHNSCC lymph node metastases. High‐risk HPV subtypes are not associated with p16 positivity and do not appear to play a role in this disease. HPV testing, in addition to the p16 status in the unknown primary setting, may provide additional information for determining a putative primary site. Cancer 2016;122:1201–8 . © 2016 American Cancer Society . Abstract : Cervical lymphadenopathy secondary to cutaneous head and neck squamous cell carcinoma frequently exhibits p16 positivity (31%), but this positivity is not associated with an improved outcome. High‐risk human papillomaviruses are not associated with node‐positive cutaneous squamous cell carcinoma, regardless of the p16 status.